Tropical Dry Forest Resilience to Fire Depends on Fire Frequency and Climate - Hartung, Maximilian; Carreño-Rocabado, Geovana; Peña-Claros, Marielos; van der Sande, Masha T. (Frontiers in Forests and Global Change, 2021)
Wildfires are becoming increasingly frequent and devastating in many tropical forests. Although seasonally dry tropical forests (SDTF) are among the most fire-threatened ecosystems, their long-term response to frequent wildfires remains largely unknown. This study is among the first to investigate the resilience in response to fire of the Chiquitano SDTF in Bolivia, a large ecoregion that has seen an unprecedented increase in fire intensity and frequency in recent years. We used remote sensing data to assess at a large regional and temporal scale (two decades) how fire frequency and environmental factors determine the resilience of the vegetation to fire disturbance. Resilience was measured as the resistance to fire damage and post-fire recovery. Both parameters were monitored for forested areas that burned once (F1), twice (F2), and three times (F3) between 2000 and 2010 and compared to unburned forests. Resistance and recovery were analyzed using time series of the Normalized Burn Ratio (NBR) index derived from Landsat satellite imagery, and climatic, topographic, and a human development-related variable used to evaluate their influence on resilience. The overall resilience was lowest in forests that burned twice and was higher in forests that burned three times, indicating a possible transition state in fire resilience, probably because forests become increasingly adapted during recurrent fires. Climatic variables, particularly rainfall, were most influential in determining resilience. Our results indicate that the Chiquitano dry forest is relatively resilient to recurring fires, has the capacity to recover and adapt, and that climatic differences are the main determinants of the spatial variation observed in resilience. Nevertheless, further research is needed to understand the effect of the higher frequency and intensity of fires expected in the future due to climate change and land use change, which may pose a greater threat to forest resilience.